2008
DOI: 10.1016/j.rapm.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Guidance Improves the Success Rate of Interscalene Brachial Plexus Blockade

Abstract: The use of ultrasound to guide needle placement and monitor the spread of local anesthetic improves the success rate of interscalene brachial plexus block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 13 publications
5
138
0
5
Order By: Relevance
“…These findings are similar to those of Kapral et al [18], who obtained 98% and 91% effective IBPBs with dual guidance and PNS confirmation alone, respectively, by administering 20 mL of 0.75% ropivacaine for trauma-related upper arm surgery. In contrast, Mejía-Terrazas et al [19] observed no difference in success rates between IBPBs performed with PNS assistance or ultrasound guidance.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to those of Kapral et al [18], who obtained 98% and 91% effective IBPBs with dual guidance and PNS confirmation alone, respectively, by administering 20 mL of 0.75% ropivacaine for trauma-related upper arm surgery. In contrast, Mejía-Terrazas et al [19] observed no difference in success rates between IBPBs performed with PNS assistance or ultrasound guidance.…”
Section: Discussionsupporting
confidence: 90%
“…In one large series (n = 5,964), Burgher et al 3 (Table 1). [2][3][4][5][6][7] By allowing the operator to visualise the nerve, needle and local anaesthetic spread, ultrasound guidance has been shown to improve the success and onset time for single shot nerve blocks of the upper 8,9 and lower 10 limbs. This has led many authors to advocate using ultrasonography for continuous nerve blocks as well.…”
Section: Discussionmentioning
confidence: 99%
“…C5 and C6 are the nerve roots of the brachial plexus. sensation and loss of motor function were assessed using the system that Kapral et al established [4]. Sensory dermatomes from C5 to C8 in the blocked arm were compared with similar dermatomes in the contralateral arm using pinprick (with a 21-G blunted needle) and a scale with 100% being normal sensation and 0% being insensate.…”
Section: Methodsmentioning
confidence: 99%
“…Motor block was evaluated by thumb abduction (radial nerve), thumb adduction (ulnar nerve), thumb opposition (median nerve), forearm supination or pronation (radial and median nerves) and shoulder abduction (axillary nerve). Motor function was evaluated using a seven-point scale developed by Kapral et al, where '6' is normal muscle force, '5' is slightly reduced muscle force, '4' is greatly reduced muscle force, '3' is slightly impaired mobility, '2' is greatly impaired mobility, '1' is near complete paralysis and '0' is complete paralysis [4].…”
Section: Methodsmentioning
confidence: 99%